ChemInform Abstract: Crystal and Magnetic Structure of Sr2MIrO6 (M: Ca, Mg) Double Perovskites — A Neutron Diffraction Study. Issue 9 (4th March 2014) - Kayser, Paula; Martinez‐Lope, Maria Jesus; Alonso, Jose Antonio; Retuerto, Maria; Croft, Mark; Ignatov, Alexander; Fernandez‐Diaz, Maria Teresa
Abstract Polycrystalline Sr2CaIrO6 (I) and Sr2MgIrO6 (II) are prepared from citrate‐nitrate precursors using Sr(NO3)2, IrO2, CaCO3, or MgO in aqueous citric acid and HNO3 evaporated at 140 °C and heated to 600 °C to decompose organic residues and NO3 (950 °C, 12 h, O2 pressure of 200 bar (I), 800 °C, 36 h for (II)).